Orbital-hybridized electron bridge enables functional compartmentalization for ultradeep electrosorption - Bijie Bie; Xiaodong Xie; Shuncai Luo; Qingtan Xu; Song Xie; Yaping Miao; Xuming Zhang; Biao Gao; Zhaobo Wang; Buxiao Kuang; Fang Zhou; Liwei Xiong; et al. (Chemical Engineering Journal, 2026)

Anomalous contaminant transport in fractured porous media: Insight from asynchronous hydraulic changes in fractures and rock matrix - Lei Ma; Di Han; Qiankun Luo; Yaping Deng; Yunhai Fang; Chao Zhang; Jiazhong Qian (Journal of Contaminant Hydrology, 2026)

Chemically converted volume-resilience interface enables high-capacity zinc anode - Mingzhu Li; Xinyue Dou; Zhexuan Liu; Yaping Wang; Shuquan Liang; Guozhao Fang (Science Bulletin, 2026)

Preparation and application of the transistor based on D-A isoindigo copolymer/GR blend for the detection of circular tumor cell - Caiyuan Liao; Fayu Wang; Long Fang; Rong Zou; Yaping Wang; Gang Chang; Hanping He (Analytica Chimica Acta, 2026)

Life-course body shape trajectories and cerebral oxygen metabolism in community-dwelling older adults - Yifan Yan; Yaping Zhang; Xuhao Zhao; Renwei Chen; Shenghao Fang; Yi Zhou; Jingkai Huang; Fuyan Wang; Christopher Chen; Zixuan Lin; Xin Xu (GeroScience, 2026)
Obesity and lifelong body-shape fluctuation are associated with late-life structural brain damage, suggesting the involvement of metabolic pathways. The cerebral metabolic rate of oxygen (CMRO₂) reflects hemodynamic and oxidative stress and precedes structural atrophy, but its role in adiposity-related brain change remains unclear. We examined whether current and life-course adiposity relate to CMRO₂ and to structural change. A total of 303 community-dwelling adults aged 50 years and older were included. Body shape was assessed using Body Mass Index (BMI) and Body Roundness Index (BRI). Global CMRO₂ was derived from TRUST and phase-contrast MRI. T1-weighted MPRAGE provided volumetry, and medial temporal atrophy (MTA) grading. General linear models estimated associations of BMI and BRI with CMRO₂, including age interactions. Age-stratified mediation tested CMRO₂ as a mediator of adiposity to MTA associations. Body-shape trajectories at ages 25, 40, 60, and current age were modeled and related to CMRO₂ and metabolism-related regions. Adiposity was associated with lower CMRO₂: with overweight (β = -1.12 μmol/100 g/min, 95%CI = (-1.96, -0.28)) and higher BRI (β = -1.31, 95%CI = (-2.36, -0.27)) showing stronger effects with advancing age. Among participants aged 70 years, CMRO₂ mediated the association between BMI and MTA (indirect β = 0.06, 95%CI = (0.01, 0.14)). Three adulthood body-shape patterns emerged, and CMRO₂ was lower in moderate increasing (β = -11.40; 95%CI = (-20.90, -1.90)) and high-rising (β = − 12.23; 95%CI = (-23.56, -0.90)) groups. Metabolism-related regions were larger in higher-risk patterns, particularly the left hypothalamus. Greater and prolonged adiposity is linked to reduced CMRO₂ and related structural differences in older adults.

Immunotoxicity and effects of gut microbiota in chicks exposed to low doses of deoxynivalenol and 15-acetyl-deoxynivalenol - Wandi Bu; Xinyao Wu; Zhihang Zhong; Yaping Fang; Shuang Chen; Jun Jiang; Yiqun Deng (Toxicology and Applied Pharmacology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Impact of Drought on Farmers’ Livelihood Vulnerability: A Case Study of County-level Units in Western Jilin Province, China - Jiani Zhang; Yang Han; Yangang Fang; Yaping Xu; Chunlin Chen; Zhuxin Liu; Feiyu Wang; Lijuan Zhuang; Fang Huang (Chinese Geographical Science, 2025)

Hereditary non-spherocytic hemolytic anemia with GPI mutations successfully treated with allogeneic hematopoietic stem cell transplantation: a first report of two cases - Huimin Li; Jiali Wang; Liucheng Rong; Jian Li; Yao Xue; Yongjun Fang; Yaping Wang (Journal of Molecular Medicine, 2025)

Comparative investigation on the adsorption behavior of bromate in aqueous solutions using Zn/Ni/Al-LDH and Ni/Al-LDH: optimization, equilibrium analysis, and mechanistic insights - Yaping Qin; Huixue Ren; Shengyun Jiang; Yuxin Bi; Chuntong Li; Rui Fang (Journal of Environmental Health Science and Engineering, 2025)

Gonadal expression profiles reveal the underlying mechanisms of temperature effects on sex determination in the large-scale loach (Paramisgurnus dabryanus) - Lei Zhang; Yutong Fang; Mijuan Shi; Keyi Ren; Xin Guan; Waqar Younas; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Animal Reproduction Science, 2025)

Effects of 2,4,6-Trichloroanisole on the morphological development and motility of zebrafish - Yanxia Zuo; Fang Zhou; Rong Huang; Zhihui Jia; Juhong Xie; Guangxin Wang; Shuzhao Jia; Yongming Li; Manyi Wang; Lanjie Liao; Feng Ge; Yaping Wang (Science of The Total Environment, 2024)

Therapeutic Effect of Smilax glabra Roxb. on Weaning Rats Against Pb-Induced Nephrotoxicity Based on Network Pharmacology - Chongmei Tian; Meiting Yu; Yuejuan Fang; Yaping Zhao; Liping Fu; Jingbai Chen; Daozong Xia (Biological Trace Element Research, 2024)

Bacterial community network complexity and role of stochasticity decrease during primary succession - Yucheng He; Binu M. Tripathi; Jie Fang; Zihao Liu; Yaping Guo; Yue Xue; Jonathan M. Adams (Soil Ecology Letters, 2024)

Relationship of environmental exposure temperature and temperature extremes on sperm DNA fragmentation index in men with different BMI values and the indirect effect of DNA fragmentation index on semen parameters - Chen Wang; Qiwei Yu; Ting Chu; Fang Wang; Fangli Dong; Hang Xin; Di Wang; Yaping Liu; Jun Zhai (Science of The Total Environment, 2024)

Distinct biogeographic patterns in Glomeromycotinian and Mucoromycotinian arbuscular mycorrhizal fungi across China: A meta-analysis - Zihao Liu; Jie Fang; Yucheng He; Gary D. Bending; Bin Song; Yaping Guo; Xiaojie Wang; Zemin Fang; Jonathan M. Adams (Science of The Total Environment, 2024)

Identification of high-permeability and water-rich zones in a fractured karst water source area based on the hydraulic tomography method - Lei Ma; Xiaofan Sun; Jiazhong Qian; Wei Wang; Yaping Deng; Yunhai Fang (Journal of Hydrology, 2024)

The role of HBV cccDNA in occult hepatitis B virus infection - Pei He; Peixin Zhang; Yaping Fang; Ning Han; Wensu Yang; Zhaoxin Xia; Yi Zhu; Zhenhua Zhang; Jilu Shen (Molecular and Cellular Biochemistry, 2023)

AraENCODE: A comprehensive epigenomic database of Arabidopsis thaliana - Zhenji Wang; Minghao Liu; Fuming Lai; Qiangqiang Fu; Liang Xie; Yaping Fang; Qiangwei Zhou; Guoliang Li (Molecular Plant, 2023)

Effect of combined zinc oxide nanoparticles using citric acid and microwave heating on the quality of animal fat - Lan Zhang; Min Zhang; Yaping Liu; Zhongxiang Fang (Food Bioscience, 2023)

Elevated CO2 and temperature increase arbuscular mycorrhizal fungal diversity, but decrease root colonization, in maize and wheat - Zihao Liu; Zhenhua Yu; Bin Song; Yansheng Li; Jie Fang; Yaping Guo; Jian Jin; Jonathan M. Adams (Science of The Total Environment, 2023)

Quantification of solute transport in a fracture-matrix system using geoelectrical monitoring - Yongshuai Yan; Jiazhong Qian; Lei Ma; Guizhang Zhao; Yaping Deng; Haoming Zhang; Yunhai Fang; Yong Liu (Journal of Hydrology, 2023)

Transcriptome Analysis Reveals Differential Gene Expression in Garlic Aerial Bulbs in Response to Gibberellin Application - Yuhui Dong; Hongcheng Fang; Yujiao Hou; Yaping Zhao; Xiudong Sun; Shiqi Liu (Journal of Plant Growth Regulation, 2022)

Gene expression in the microbial consortia of colonial Microcystis aeruginosa ‐a potential buoyant particulate biofilm - Limei Shi; Yuanfeng Cai; Shengling Gao; Daoyan Fang; Yaping Lu; Pengfu Li; Qinglong L. Wu (Environmental Microbiology, 2022)
Microcystis spp., notorious bloom‐forming cyanobacteria, are often present in colony form in eutrophic lakes worldwide. Uncovering the mechanisms underlying Microcystis colony formation and maintenance is vital to controlling the blooms, but it has long been a challenge. Here, bacterial communities and gene expression patterns of colonial and unicellular forms of one non‐axenic strain of Microcystis aeruginosa isolated from Lake Taihu were compared. Evidently, different microbial communities between them were observed through 16S rDNA MiSeq sequencing. Metatranscriptome analyses revealed that transcripts for pathways involved in bacterial biofilm formation, such as biosynthesis of peptidoglycan and arginine by Bacteroidetes , methionine biosynthesis, alginate metabolism, flagellum, and motility, as well as widespread colonization islands by Proteobacteria , were highly enriched in the colonial form. Furthermore, transcripts for nitrogen fixation and denitrification pathways by Proteobacteria that usually occur in biofilms were significantly enriched in the colonial Microcystis . Results revealed that microbes associated with Microcystis colonies play important roles through regulation of biofilm‐related genes in colony formation and maintenance. Moreover, Microcystis colony represents a potential ‘buoyant particulate biofilm’, which is a good model for biofilm studies. The biofilm features of colonial Microcystis throw a new light on management and control of the ubiquitous blooms in eutrophic waters.

The Potential of Kelp Saccharina japonica in Shielding Pacific Oyster Crassostrea gigas From Elevated Seawater pCO2 Stress - Zengjie Jiang; Weiwei Jiang; Samuel P. S. Rastrick; Xiaoqin Wang; Jinghui Fang; Meirong Du; Yaping Gao; Yuze Mao; Øivind Strand; Jianguang Fang (Frontiers in Marine Science, 2022)
Ocean acidification (OA) caused by elevated atmospheric CO 2 concentration is predicted to have negative impacts on marine bivalves in aquaculture. However, to date, most of our knowledge is derived from short-term laboratory-based experiments, which are difficult to scale to real-world production. Therefore, field experiments, such as this study, are critical for improving ecological relevance. Due to the ability of seaweed to absorb dissolved carbon dioxide from the surrounding seawater through photosynthesis, seaweed has gained theoretical attention as a potential partner of bivalves in integrated aquaculture to help mitigate the adverse effects of OA. Consequently, this study investigates the impact of elevated p CO 2 on the physiological responses of the Pacific oyster Crassostrea gigas in the presence and absence of kelp ( Saccharina japonica ) using in situ mesocosms. For 30 days, mesocosms were exposed to six treatments, consisting of two p CO 2 treatments (500 and 900 μatm) combined with three biotic treatments (oyster alone, kelp alone, and integrated kelp and oyster aquaculture). Results showed that the clearance rate (CR) and scope for growth (SfG) of C. gigas were significantly reduced by elevated p CO 2 , whereas respiration rates (MO 2 ) and ammonium excretion rates (ER) were significantly increased. However, food absorption efficiency (AE) was not significantly affected by elevated p CO 2 . The presence of S. japonica changed the daytime pH NBS of experimental units by ~0.16 units in the elevated p CO 2 treatment. As a consequence, CR and SfG significantly increased and MO 2 and ER decreased compared to C. gigas exposed to elevated p CO 2 without S. japonica. These findings indicate that the presence of S. japonica in integrated aquaculture may help shield C. gigas from the negative effects of elevated seawater p CO 2 .

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

A 2-step algorithm combining glutamate dehydrogenase and nucleic acid amplification tests for the detection of Clostridioides difficile in stool specimens - Chengcheng Liu; Chenjie Tang; Yaping Han; Yuqiao Xu; Fang Ni; Ke Jin; Genyan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Assessing the effects of oyster/kelp weight ratio on water column properties: an experimental IMTA study at Sanggou Bay, China - Jinghui Fang; Jianguang Fang; Qionglin Chen; Yuze Mao; Zengjie Jiang; Meirong Du; Yaping Gao; Fan Lin (Journal of Oceanology and Limnology, 2020)

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

Simulation of Yesso scallop, Patinopecten yessoensis, growth with a dynamic energy budget (DEB) model in the mariculture area of Zhangzidao Island - Weiwei Jiang; Fan Lin; Meirong Du; Jianguang Fang; Jinghui Fang; Yaping Gao; Xiaoqin Wang; Fengxue Li; Shipeng Dong; Xing Hou; Zengjie Jiang (Aquaculture International, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Myelin Oligodendrocyte Glycoprotein-IgG Contributes to Oligodendrocytopathy in the Presence of Complement, Distinct from Astrocytopathy Induced by AQP4-IgG - Ling Fang; Xinmei Kang; Zhen Wang; Shisi Wang; Jingqi Wang; Yifan Zhou; Chen Chen; Xiaobo Sun; Yaping Yan; Allan G. Kermode; Lisheng Peng; Wei Qiu (Neuroscience Bulletin, 2019)

Response of Yesso scallop Patinopecten yessoensis to acute temperature challenge: physiological and biochemical parameters - Weiwei Jiang; Meirong Du; Jianguang Fang; Yaping Gao; Yuze Mao; Qionglin Chen; Fan Lin; Zengjie Jiang (Journal of Oceanology and Limnology, 2019)

Photosynthetic and metabolic responses of eelgrass Zostera marina L. to short-term high-temperature exposure - Yaping Gao; Zengjie Jiang; Meirong Du; Jinghui Fang; Weiwei Jiang; Jianguang Fang (Journal of Oceanology and Limnology, 2019)

Selectivity of Perinereis aibuhitensis (Polychaeta, Nereididae) feeding on sediment - Jinghui Fang; Zengjie Jiang; Jianguang Fang; Bin Kang; Yaping Gao; Meirong Du (Marine Biology Research, 2018)

Size fraction of phytoplankton and the contribution of natural plankton to the carbon source of Zhikong scallop Chlamys farreri in mariculture ecosystem of the Sanggou Bay - Zengjie Jiang; Meirong Du; Jinghui Fang; Yaping Gao; Jiaqi Li; Li Zhao; Jianguang Fang (Acta Oceanologica Sinica, 2017)

Applicability of Perinereis aibuhitensis Grube for fish waste removal from fish cages in Sanggou Bay, P. R. China - Jinghui Fang; Zengjie Jiang; Henrice M. Jansen; Fawen Hu; Jianguang Fang; Yi Liu; Yaping Gao; Meirong Du (Journal of Ocean University of China, 2017)

Environmental remediation potential of Perinereis aibuhitensis (Polychaeta) based on the effects of temperature and feed types on its carbon and nitrogen budgets - Jinghui Fang; Jihong Zhang; Zengjie Jiang; Meirong Du; Yi Liu; Yuze Mao; Yaping Gao; Jianguang Fang (Marine Biology Research, 2016)

Tolerance, oxygen consumption and ammonia excretion of Ophiopholis sarsii vadicola in different temperatures and salinities - Jinghui Fang; Jihong Zhang; Zengjie Jiang; Xuewei Zhao; Xu Jiang; Meirong Du; Yaping Gao; Jianguang Fang (Journal of Ocean University of China, 2015)

Development of 39 novel polymorphic microsatellite markers for the giant mottled eel Anguilla marmorata and cross-amplification in other eel species - Xiaolu Wang; Fang Xu; Li Li; Yaping Zhang; Yandong Ding; Xue Zang; Yihe Jia; Guosong Zhang; Yayuan Wang; Xiaojun Wang; Hongwei Zhang; Shaowu Yin (Conservation Genetics Resources, 2014)

Hepatocyte Nuclear Factor 4 Alpha and Farnesoid X Receptor Co-regulates Gene Transcription in Mouse Livers on a Genome-Wide Scale - Ann M. Thomas; Steve N. Hart; Guodong Li; Hong Lu; Yaping Fang; Jianwen Fang; Xiao-bo Zhong; Grace L. Guo (Pharmaceutical Research, 2013)

Geological events play a larger role than P leistocene climatic fluctuations in driving the genetic structure of Q uasipaa boulengeri ( A nura: D icroglossidae) - Fang Yan; Weiwei Zhou; Haitao Zhao; Zhiyong Yuan; Yunyu Wang; Ke Jiang; Jieqiong Jin; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Paleoclimatic and paleogeological events have been identified as being the two main drivers of genetic structuring in extant organisms. We used a montane stream‐dwelling frog, Q uasipaa boulengeri , to explore the relative roles played by these drivers on species in southern C hina, a region needing thorough studies. We detected four major matrilines, and no broadly distributed haplotypes occurred. The complex orogenesis of south‐western China drove matrilineal divergence in Q . boulengeri into highly structured geographical units. These matrilines subsequently persisted in situ with stable populations rather than undergoing expansions during glacial cycling. The unification of the upper and middle Y angtze R iver in the Three Gorges mountain region mediated downstream colonization of this frog. Analyses identified geological events as playing a larger role than climatic fluctuations in driving the population history of Q . boulengeri . Nuclear allele analyses indicated gene flow; this maintained genetic cohesion of the species. S outh‐eastern S ichuan B asin was identified as the area of secondary contact for several matrilines, and this area deserves further study and special protection.

Antigenic analysis of grass carp reovirus using single-chain variable fragment antibody against IgM from Ctenopharyngodon idella - CongLin Chen; XiaoYun Sun; LanJie Liao; ShaoXiang Luo; ZhouQuan Li; XiaoHua Zhang; YaPing Wang; QionLin Guo; Qin Fang; HePing Dai (Science China Life Sciences, 2013)

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

Growth and loss of mariculture kelp Saccharina japonica in Sungo Bay, China - Jihong Zhang; Jianguang Fang; Wei Wang; Meirong Du; Yaping Gao; Mingliang Zhang (Journal of Applied Phycology, 2012)

Novel parvovirus sublineage in the family of Parvoviridae - Fang Wang; Yongwei Wei; Chun Zhu; Xianbo Huang; Yaping Xu; Lian Yu; Xuping Yu (Virus Genes, 2010)

Maternal cigarette smoking, metabolic gene polymorphisms, and preterm delivery: new insights on G×E interactions and pathogenic pathways - Hui-Ju Tsai; Xin Liu; Karen Mestan; Yunxian Yu; Shanchun Zhang; Yaping Fang; Colleen Pearson; Katherin Ortiz; Barry Zuckerman; Howard Bauchner; Sandra Cerda; Phillip G. Stubblefield; et al. (Human Genetics, 2008)